Fish culture technologies in South-eastern Nigeria (African Journal of Fisheries Science, 2019)
Aquaculture has become an important sector in Nigerian economy and is considered a means of bridging the gap between the supply and demand for fish since the wild stock is fast declining. The study was carried out to assess the status, structure, operation and management options of fish culture systems in three zones of South-east Nigeria and to determine the impact on the economy of the region. Results shows that the number of operational fish ponds in the region was estimated to be 346 consisting of 205 extensive, 105 semi-intensive and 36 intensive fish farms with majority of culturist operating at subsistence level. Common fish cultured were Clarias gariepinus, Heterobranchus longifilis, Heteroclarias, Oreochromis niloticus, Clarias anguillaris and Hemichromis fasciatus. O. niloticus was most common in all zones accounting for 91.6% while Heteroclarias culture was practiced only in Zone C. Earthen ponds were most common in Zone A and accounted for 40.9% while majority of farms (33.3%) in Zone C raised their fish in concrete ponds. More farms in Zone C adopted flow through system constituting 51.9% while stagnant ponds accounted for 74.2 and 56.8% of ponds in Zones A and B, respectively. Most common culture systems in the three zones were polycultured. Rainfall was major source of water in Zone A (71.0%) while rivers/streams were the common sources for culturist in Zones B (52.3%) and C (53.3%). However, well water and borehole take the lead as sources of water during the dry season. Males were the dominant sex among culturists and majority, were of ages between 40 and 70 years. Secondary school education was the least among culturists and fish farm activity was predominantly part-time (61.8%). Low income farmers were dominant in Zone A (79.0%) while majority of farmers (85.7%) in Zone C were high income. Personal savings was the most important source of financing farm operation among fish producers in Zone A (63.8%) while Bank loan was the common (56.3%) source of finance in Zone C. Therefore, to encourage new entrants especially the unemployed in the rural communities to start the enterprise, urgent steps must be taken to make credit facility available.